Bibliometric Analysis: Effectiveness of Belimbing Wuluh (Averrhoa Bilimbi L.) Leaves in Wound Healing - Setyaningtyas, Rahma Julia; Soesanto, Edy; Armiyati, Yunie (Universitas Muhammadiyah Semarang, 2023)
The use of medicinal plants as a complementary therapy or adjuvant treatment is also increasingly popular among people who are looking for a holistic and natural treatment approach. Belimbing wuluh leaves have potential as a natural ingredient for wound healing. Research mapping related to the effectiveness of starfruit leaves in the wound healing process with a bibliometric analysis approach is needed to see how much and to what extent research has been carried out and to find updates that can be carried out for further research. The aim of this research is to explore the trend of the number of publications, which fields are most approved for publication, network visualization, overlay visualization, and density visualization on the topic of the effectiveness of starfruit leaves and wound healing through bibliometric analysis. This research method uses bibliometric data analysis. The data source used in this study was based on an online search via https://app.dimensions.ai/. Data collection was carried out on July 14, 2023. The literature search used the stages following the Preferred Reporting Items for Systematic Review and Meta-Analyses flowchart. A search for publications related to the effectiveness of starfruit leaves and wound healing resulted in 709 articles. After screening through the specified criteria, a total of 23 articles were obtained. Research on the effectiveness of starfruit leaves and wound healing is not only carried out by the fields of medicine, veterinary medicine, public health or nurses but also by other fields. Fields such as chemistry, biological sciences, agriculture, food science, and biomedical sciences. In addition, current trends in the effectiveness of starfruit leaves and wound healing focus on the effects of treatments, traditional medicines and plants in Indonesia.